Evaluation of Prophylactic Antibiotic in Caesarean Section - Ansari, Nazmussaba; Das, CR; Ansari, Miraj Alam (Journal of Nepalgunj Medical College, 2016)
Introduction: Caesarean section is one of the most rewarding surgeries when performed in time and indication. The number of C/S has been growing rapidly in the developing as well as developed world. Aims & Objectives: Evaluation of prophylactic antibiotic in caesarean section. Methodology: This study was conducted in Nepalgunj Medical College Teaching Hospital, Kohalpur from June 2014 to September 2014. Group A consisted of 100 patient who were randomly allocated & injection ceftriaxone 1gm. I/V stat was given at the time of induction of anesthesia (30 mins. before incision). Group B also consisted of 100 patients who were given 5 days antibiotics. Results: In post operative evaluation the infection rate were compared in both groups, group A wound infection 2% and group B 3% , Endometritis - group A 1% and group B 2%, UTI- group A 3% and group B 4%, Fever - group A 6% and group B 4%. Conclusion: Single dose prophylactic antibiotic is comparable to multi dose antibiotic in this study. Since the single dose antibiotic is as efficacious as multi dose regime, it is advocated that single dose prophylactic antibiotic can be given in caesarean section as it is cost effective and as efficient as multi dose regimen. JNGMC Vol. 12 No. 2 December 2014, Page: 40-41